The pedagogy of the Landless Workers' Movement and the contributions of the educational thought of M. M. Pistrak - Lidianny Nascimento Fonseca; Mário Borges Netto (Universidade Federal do Norte do Tocantins, 2024)
The purpose of this article is to reflect on the contributions of Pistrak's (2011) educational thinking to the development of the pedagogical proposal of the Movimento Sem Terra (MST), highlighting how the MST draws inspiration from the theories of the Soviet pedagogue in shaping its proposal. Additionally, the text discusses Marx's (2013) concept of omnilateral education, which involves the comprehensive formation of the human being in all its dimensions. The analysis presented emphasizes how the educational proposal of the MST contrasts with the capitalist educational model, focusing on the self-organization of learners, the relationship between school and social practice, and education geared towards social transformation. The methodology employed in this research consisted of descriptive research, combined with bibliographic and documentary approaches. The analysis of the collected data was conducted through the application of Historical-Dialectical Materialism as the main analytical tool. The results indicate that the MST experiments with and promotes the theoretical and methodological foundations of socialist pedagogy. It underscores the movement's commitment to the working class, its struggle for agrarian reform and education, and how the pedagogical proposal aligns with the movement's political project in pursuit of deeper social transformations. The analysis also highlights the importance of forming individuals engaged in social transformation, and the direct connection between MST education and socialist principles.